Spatiotemporal variation and tendency analysis on rainfall erosivity in the Loess Plateau of China - Yongsheng Cui (Hydrology Research, 2020)
Rainfall erosivity is an important factor to be considered when predicting soil erosion. Precipitation data for 1971–2010 from 39 stations located in the Loess Plateau of China were collected to calculate the spatiotemporal variability of rainfall erosivity, and the long-term tendency of the erosivity was predicted using data from the HadGEM2-ES model. Statistical analyses were done using Mann–Kendall statistic tests and ordinary Kriging interpolation. The results showed that the annual mean rainfall erosivity in the Loess Plateau decreased from 1,286.02 MJ mm hm−2 h−1 a−1 in 1971–1990 to 1,201.46 MJ mm hm−2 h−1 a−1 in 1991–2010 and mainly occurred in July to August. The rainfall erosivity decreased from the southeast to the northwest of the Loess Plateau and was closely related to the annual precipitation amount. However, the effect of annual precipitation on rainfall erosivity weakened under climate change: the annual precipitation increased and the rainfall erosivity decreased. Climate change, however, had little influence on the spatial variation in rainfall erosivity in the Loess Plateau. The results obtained can facilitate the prediction of spatial and temporal variations in soil erosion in the Loess Plateau. HIGHLIGHTS Both precipitation and rainfall erosivity showed an insignificant decreasing trend for 1971–2010.; The climate model predicts an increasing precipitation but decreasing rainfall erosivity.; South and southeast of the Loess Plateau are areas susceptible to rainfall erosion under climate change.;